Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T22:12:50+01:00
W(x)= (3x^3 - 3x^2 + x - 1) - ( 6x^3 + 15x^2 + 2x + 5) =
= 3x^3 - 3x^2 + x - 1 - 6x^3 - 15x^2 - 2x - 5 = -3x^3 - 18x^2 - x - 6

w(x)= (x^3 + 6x + 2x^2 + 12) - ( x - 2x^3 + 2 - 4x^2)=
= x^3 + 6x + 2x^2 + 12 - x + 2x^3 - 2 + 4x^2 = 3x^3 + 5x + 6x^2 + 10

w(x)= ( x^3 + 3x^2 + x + 3) - ( 4x - 3x^3 + 12 - 9x^2)=
= x^3 + 3x^2 + x + 3 - 4x +3x^3 - 12 + 9x^2 = 4x^3 + 12x^2 - 3x - 9

Mam nadzieję że nigdzie nie popełniłam błędu ;-)
1 5 1
2010-01-20T00:14:03+01:00
W(x)=(3x^3 - 3x^2 + x - 1) - ( 6x^3 + 15x^2 + 2x + 5)=
=3x^3 - 3x^2 + x - 1 - 6x^3 - 15x^2 - 2x - 5 = -3x^3 - 18x^2 - x - 6

w(x)=(x^3 + 6x + 2x^2 + 12) - ( x - 2x^3 + 2 - 4x^2)=
=x^3 + 6x + 2x^2 + 12 - x + 2x^3 - 2 + 4x^2 = 3x^3 + 5x + 6x^2 + 10

w(x)=( x^3 + 3x^2 + x + 3) - ( 4x - 3x^3 + 12 - 9x^2)=
=x^3 + 3x^2 + x + 3 - 4x +3x^3 - 12 + 9x^2 = 4x^3 + 12x^2 - 3x - 9
1 5 1